PARADOX OF MODERNITY IN IKBAL - Abdüllatif TÜZER (Fırat University, 2019)
Muhammed Iqbal is the most leading and eminent Muslim entellectual, thinker, poet and politician of twentieth century. We find his prominence, with regard to especially his entellectual character, in his major project: Reconstruction and Modernisation of Islam. Though Islam is potentially capable of constructing a great civilization, Muslims in modern era are miserable and on the brink of collapse and grave. Ikbal's ideal, however, is construction of a great and majestic civilization of union as Islamically oriented and identified. He finds the West as inadequate to generate the union of humankind. Because the western in